1989
DOI: 10.1038/342072a0
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of two distinct Ca2+ -ATPase-like proteins and their relationships to the agonist-sensitive calcium store in adrenal chromaff in cells

Abstract: Many cellular functions are regulated by activation of cell-surface receptors that mobilize calcium from internal stores sensitive to inositol 1,4,5-trisphosphate (Ins(1,4,5)P3). The nature of these internal calcium stores and their localization in cells is not clear and has been a subject of debate. It was originally suggested that the Ins(1,4,5)P3-sensitive store is the endoplasmic reticulum, but a new organelle, the calciosome, identified by its possession of the calcium-binding protein, calsequestrin, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
64
3

Year Published

1990
1990
2000
2000

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(79 citation statements)
references
References 24 publications
12
64
3
Order By: Relevance
“…(iii) Ca 2+ release from alveolar sacs (Länge et al, 1995) shares some other properties with Ca 2+ channels in the SR (Rousseau & Meissner, 1989), like stimulation by ATP and inhibition by Mg 2+ . (iv) In cells with only diffusely distributed ER, the signal produced by caffeine is diffuse (Burgoyne et al, 1989), i.e., quite different from what we see. Concomitantly, restriction of the Ca 2+ signal in time and space, as we have documented, is in contradiction to what would be expected from diffuse activation.…”
Section: Does Caffeine Mobilize Subcortical Ca 2+ Stores?contrasting
confidence: 50%
“…(iii) Ca 2+ release from alveolar sacs (Länge et al, 1995) shares some other properties with Ca 2+ channels in the SR (Rousseau & Meissner, 1989), like stimulation by ATP and inhibition by Mg 2+ . (iv) In cells with only diffusely distributed ER, the signal produced by caffeine is diffuse (Burgoyne et al, 1989), i.e., quite different from what we see. Concomitantly, restriction of the Ca 2+ signal in time and space, as we have documented, is in contradiction to what would be expected from diffuse activation.…”
Section: Does Caffeine Mobilize Subcortical Ca 2+ Stores?contrasting
confidence: 50%
“…There is convincing evidence that intracellular Ca 2+ stores are heterogeneous [6] and in bovine adrenal chromaffin cells two immunologically distinct Ca 2+-ATPases with different subcellular distribution have been reported [16]. Our results suggest that tBuBHQ inhibits Ca 2+ uptake by a fraction (about 80070) of intracellular stores that includes, but is not restricted to, the Ins(1,4,5)P3-sensitive stores.…”
Section: Resultssupporting
confidence: 48%
“…Both of these stimuli lead to Ca 2+ activation of the subplasmalemmal exocytotic sites [2,3]. In contrast, the InsPrmobilizing agonist angiotensin II results in either no secretion or a polarized secretory response as the InsP3-sensitive store [3,5] and the intracellular Ca 2÷ signal [4] are spatially restricted. We have previously shown that, in addition to the InsP3-sensitive store, these cells also possess a caffeinesensitive Ca 2÷ store that is diffusely distributed throughout the cell [5].…”
Section: Introductionmentioning
confidence: 99%